The Influence of Brand Ambassador, Brand Awareness on Purchasing Decisions Moderate Brand Image - I Komang Dani Surya Miarta; Ni Ketut Seminari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Brand ambassador, as a direct representation of the brand, and brand awareness, the level of consumer awareness of the brand, were identified as potential factors influencing consumer purchasing decisions. The concept of brand image, which reflects the overall image of a brand in consumers' minds, is thought to moderate the relationship between brand ambassadorship, brand awareness, and purchasing decisions. The research method uses a quantitative approach by collecting data through surveys with a sample of consumers who have been exposed to brand ambassador activities and information about the brand. The research results show that brand ambassadors and brand awareness have a positive and significant effect on purchasing decisions; and the interaction of brand ambassadors with brand image on purchasing decisions shows that brand image moderates the influence of brand ambassadors on purchasing decisions; and the interaction of brand awareness with brand image on purchasing decisions shows that brand image moderates the influence of brand awareness on purchasing decisions. This research provides practical implications for brand management in designing more effective marketing strategies.